Thomas Aquinas's Summa theologiae : A Biography - McGinn, Bernard, 1937- (Book collections on Project MUSE., 2014)
This concise book tells the story of the most important theological work of the Middle Ages, the vast Summa theologiae of Thomas Aquinas, which holds a unique place in Western religion and philosophy. Written between 1266 and 1273, the Summa was conceived by Aquinas as an instructional guide for teachers and novices and a compendium of all the approved teachings of the Catholic Church. It synthesizes an astonishing range of scholarship, covering hundreds of topics and containing more than a million and a half words--and was still unfinished at the time of Aquinas's death. Here, Bernard McGinn, one of today's most acclaimed scholars of medieval Christianity, vividly describes the world that shaped Aquinas, then turns to the Dominican friar's life and career, examining Aquinas's reasons for writing his masterpiece, its subject matter, and the novel way he organized it. McGinn gives readers a brief tour of the Summa itself, and then discusses its reception over the past seven hundred years. He looks at the influence of the Summa on such giants of medieval Christendom as Meister Eckhart, its ridicule during the Enlightenment, the rise and fall of Neothomism in the nineteenth and twentieth centuries, the role of the Summa in the post-Vatican II church, and the book's enduring relevance today.